A Randomized Controlled Trial of an Electronic Informed Consent Process. (December 2014) - Rothwell, Erin; Wong, Bob; Rose, Nancy C.; Anderson, Rebecca; Fedor, Beth; Stark, Louisa A.; Botkin, Jeffrey R.
A pilot study assessed an electronic informed consent model within a randomized controlled trial (RCT). Participants who were recruited for the parent RCT project were randomly selected and randomized to either an electronic consent group ( n = 32) or a simplified paper-based consent group ( n = 30). Results from the electronic consent group reported significantly higher understanding of the purpose of the study, alternatives to participation, and who to contact if they had questions or concerns about the study. However, participants in the paper-based control group reported higher mean scores on some survey items. This research suggests that an electronic informed consent presentation may improve participant understanding for some aspects of a research study.